Impact of tooth loss due to periodontal disease on the prognosis of rehabilitation - Cimões, Renata; Pinho, Roberto Carlos Mourao; Gurgel, Bruno César De Vasconcelos; Borges, Samuel Batista; Júnior, Elcio Marcantonio [UNESP]; Marcantonio, Camila Chierici [UNESP]; Melo, Marcelo Augusto Ruiz Da Cunha; Piattelli, Adriano; Shibli, Jamil Awad (FapUNIFESP (SciELO), 2021)
When periodontal disease is diagnosed, it is difficult to predict the clinical response of treatment of a tooth over time because the result of treatment is affected by several factors and will depend on the maintenance and support of periodontal treatment. Rehabilitation with removable dental prostheses, fixed prostheses, and dental implants makes it possible to restore the function and esthetics of patients with tooth loss due to periodontal disease. The predictive factors of tooth loss in periodontitis patients should be assessed by dentists to inform their clinical decision-making during dental treatment planning. This will provide detailed individualized information and level of risk of patients considered suitable for dental rehabilitation. Therefore, the aim of this article was to review the subject of “Impact of tooth loss due to periodontal disease on the prognosis of rehabilitation” and the effect of fixed, removable, and implant-supported prostheses in periodontal patients.
Keywords: Compliance; Periodontal Diseases; Prosthesis and Implants; Rehabilitation; Tooth Loss